Influence of ionic liquids on thermodynamics of small molecule DNA interaction: the binding of ethidium bromide to calf thymus DNA - Mishra, Arpit; Ekka, Mary Krishna; Maiti, Souvik (Journal of Physical Chemistry B, 2016)
Ionic liquids (ILs) are salts with poor ionic coordination, resultantly remaining in liquid state below 100 degrees C and some may retain liquid state even at room temperature. ILs are known to provide a conducive environment for many biological enzymatic reactions, but their interaction with biomacromolecules are poorly understood. In the present study, we investigate the effect of various ionic liquids on DNA small molecule interaction using calf thymus DNA (ctDNA) ethidium bromide (EB) as a model system. The effect of various ionic liquids on these interactions is studied by an array of techniques such as circular dichroism (CD), UV melting, fluorescence exclusion and isothermal titration calorimetry. Interestingly, we observed that presence of IL increased the stability of ctDNA without altering its structure. The binding affinities Kbs for EB binding to ctDNA in the presence of 300 mM ILs are about half order of magnitude smaller than the Kbs in absence of ILs and correspond to a less favorable free energy. We noted that, when adjusted to corresponding buffer condition, the unfavorable shift in AG of ctDNA-EB interaction is attributed to decreased entropy in the case of ILs, whereas the same effect by NaCI was due to increased enthalpy.

Francisella novicida Cas9 interrogates genomic DNA with very high specificity and can be used for mammalian genome editing - Acharya, Sundaram; Mishra, Arpit; Paul, Deepanjan; Ansari, Asgar Hussain; Azhar, Mohd; Kumar, Manoj; Rauthan, Riya; Sharma, Namrata; Aich, Meghali; Sinha, Dipanjali; Sharma, Saumya; Jain, Shivani; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2019)
Genome editing using the CRISPR/Cas9 system has been used to make precise heritable changes in the DNA of organisms. Although the widely used Streptococcus pyogenes Cas9 (SpCas9) and its engineered variants have been efficiently harnessed for numerous gene-editing applications across different platforms, concerns remain regarding their putative off-targeting at multiple loci across the genome. Here we report that Francisella novicida Cas9 (FnCas9) shows a very high specificity of binding to its intended targets and negligible binding to off-target loci. The specificity is determined by its minimal binding affinity with DNA when mismatches to the target single-guide RNA (sgRNA) are present in the sgRNA:DNA heteroduplex. FnCas9 produces staggered cleavage, higher homology-directed repair rates, and very low nonspecific genome editing compared to SpCas9. We demonstrate FnCas9-mediated correction of the sickle cell mutation in patient-derived induced pluripotent stem cells and propose that it can be used for precise therapeutic genome editing for a wide variety of genetic disorders.
Keywords: CRISPR Cas9; gene therapy; Genome editing; iPSCs; sickle cell anemia